Space syntax analysis of the main square of Cusco - Legoas Calcine, Sheila Pamela (2018)
The study centers around the main square in the city of Cusco. The paper investigates the role of urban configuration in shaping human behavior in build environment using “space syntax” approach that focuses mainly on the analysis of spatial relations. The method, developed by Bill Hillier and the Space Syntax department of the University College of London (UCL), provided us theoretical stance and analytical software, DepthmapX, to abstract and quantify spatial relations between areas, within the main square, in terms of syntactic properties of integration and connectivity, represented as axial lines that resemble the movement on the surface taking into account topological aspects such as adjacency and proximity. This allowed us to show the correlation between spatial configuration and subsequent human behavior, the Natural Movement determined by the urban form and the non-discursive nature of the movement guided by the sense of spatial control of highly intelligible areas.